Geographical influences on the chemical composition and antifungal activity of Xylopia aromatica (Lam.) Mart. leaf essential oil - Vieira, Maria Aparecida Ribeiro [UNESP]; Jorge, Letícia Galhardo [UNESP]; Marçon, Camila [UNESP]; Campos, Felipe Girotto [UNESP]; Rozada, Andrew Matheus Frederico; Gauze, Gisele de Freitas; Seixas, Flávio Augusto Vicente; Marques, Márcia Ortiz Mayo; Mendes, Rinaldo Poncio [UNESP]; Boaro, Carmen Silvia Fernandes [UNESP] (Elsevier, 2023)
The study assessed the chemical composition and antifungal activity of Xylopia aromatica (Lam.) Mart. leaf essential oil, which was gathered in four different locations in São Paulo, Brazil, on Candida species and, for the first time, on Cryptococcus spp. To find appropriate fungal cell enzymes for the bulk of phytoligands, molecular docking simulations were run. The output and percentage of essential oil components assessed in the same and different locations varied. Rio Bonito - RB1 essential oils are mostly composed of β-phellandrene, α and β-pinene and bicyclogermacrene. RB2, on the other hand, exhibited bicyclogermacrene, spathulenol, and undetermined 3, as well as variance in biological activity. At a dosage of 125 µg mL−1, RB1 displayed antifungal activity against the Candida krusei strain, while at a dose of 500 µg mL−1, RB1 and RB2 demonstrated antifungal activity against Cryptococcus neoformans and C. gattii isolates. Given the established resistance to fluconazole, the α and β-pinene standards demonstrated in vitro activity against C. krusei (MIC=16 µg mL−1), indicating the need for further research in this area. In silico investigations identified the enzymes sterol-14-α-demethylase and N-myristoyltransferase as potential pinenes enzymatic targets. The environment altered the biological effect of X. aromatica essential oil, implying an interaction between the components.
Keywords: Annonaceae; Candida krusei; Cryptococcus gattii; Cryptococcus neoformans; Molecular docking; Terpenes